The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ta00659f
|View full text |Cite
|
Sign up to set email alerts
|

Excellent electrocatalytic performance of metal-free thiophene–sulfur covalent organic frameworks for hydrogen evolution in alkaline medium

Abstract: The application of covalent organic framework (COF) for electrocatalytic hydrogen evolution reaction (HER) has received more attention. However, its worse catalytic performance in alkaline media is problematic for practical application....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 38 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…Some recent studies similar to NiMoP@Cu 3 P/CF are listed in Table S1 †. By comparing the performance of the catalysts, such as NiCu–P ( η 10 = 175 mV), MoP@NCF ( η 10 = 129.5 mV), Cu 3 P/N–C ( η 10 = 211.1 mV), 44 Cu 3 P@NPC-CF ( η 10 = 135.5 mV), 45 C@NiCoP ( η 10 = 46.3 mV), 46 MoS 2 -MoP/FPC ( η 10 = 144 mV), 47 JLNU-COFs ( η 10 = 136 mV), 48 etc. it was found that NiMoP@Cu 3 P/CF showed excellent HER activity in alkaline electrolyte.…”
Section: Results and And Discussionmentioning
confidence: 99%
“…Some recent studies similar to NiMoP@Cu 3 P/CF are listed in Table S1 †. By comparing the performance of the catalysts, such as NiCu–P ( η 10 = 175 mV), MoP@NCF ( η 10 = 129.5 mV), Cu 3 P/N–C ( η 10 = 211.1 mV), 44 Cu 3 P@NPC-CF ( η 10 = 135.5 mV), 45 C@NiCoP ( η 10 = 46.3 mV), 46 MoS 2 -MoP/FPC ( η 10 = 144 mV), 47 JLNU-COFs ( η 10 = 136 mV), 48 etc. it was found that NiMoP@Cu 3 P/CF showed excellent HER activity in alkaline electrolyte.…”
Section: Results and And Discussionmentioning
confidence: 99%
“…2 Compared to inorganic photocatalysts/photosensitizers, conjugated polymers show the advantages of being low cost, having an easy to tune bandgap through molecular design, and high performance. To date, a vast number of conjugated polymers have been synthesized and developed in this field, 3–6 including conjugated microporous polymers (CMPs), 7 polymeric carbon nitrides (PCNs), 8 covalent organic frameworks (COFs), 9,10 covalent triazine-based frameworks (CTFs) 11 and linear polymers. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…A covalent organic framework (COF), which is constructed from different building blocks, can present a coordinated and controllable framework and further makes the heteroatomic doping point location controllable. 24–27 In addition, the ordered structure and vertical channel array in the 2D stacked structure COF with high crystallization can provide multichannel electron migration routes. 28,29 At the same time, the larger specific surface area helps the active site in the catalyst to be in contact with the reaction medium, thus improving the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%